O intempestivo BATAILLE: êxtase orgiástico, experiência interior, erotismo e ânus solar - Barros, Lindinês Gomes de (2013)
This thesis provides a reading through the fields of social sciences, of the philosophical concepts that compose the subject erotic and orgiastic in the thought and the narrative work - out with the paradigm of civilization of Georges Bataille: eroticism, ecstasy, inner experience, excess, transgression, and solar anus. This thinker, whose works deal with an erotic intention stigmatized as both pornographic and disconcerting because it subverts the concepts of reality and normality, constituted our main theoretical and literary "corpus". Bataille proposes a decomposition of the paradigm of civilizing rationality thanks to the idiosyncratic and obscure rhythms that form his erotic subject, with impure and imperfect subjectivities. In this discussion, we address his vision that consists in eroticism recognized as an inner experience, not subdued to regulation or discipline. This type of experience causes a kind of not-knowing, which reproduces the configuration of wild singularities proposed by Foucault and related to what cannot be assimilated by institutions and cultures. The characters in his literary narrative allow us to observe and define the erotic subject at the intersection between ecstasy and inner experience. They are convulsive bodies emerging from vertigo. Impregnated with this problem, they bring Eros sovereignty with elements of tragic eroticism and of horror that plunge the subject into the unknowable and the rationalizing inapprehensible. What we question in his mind is the challenge of thinking the abject and the excremental, that escape deterministic reasoning and release the vision of contemplative ecstasy by dispelling the significant determinants and the pedagogization that intertwine the social fabric.. The thesis will present his position deliberately at the fringe, which aimed to upset the established order in theology and science. It will reveal the orgiastic itinerary created by Bataille and characterized by economy of outlay, excess, anguish, ecstasy, eroticism, inner experience and concerns. Such a philosophical intent proposes a thought of waste, consumption and reasoning that release from the human condition